Fluid Flow, Brecciation, and Shear Heating on Faults: Insights From Carbonate Clumped‐Isotope Thermometry. Issue 9 (8th September 2018) - Swanson, E. M.; Wernicke, B. P.; Eiler, J. M.
Abstract: Slip on gently dipping detachments in the brittle crust has been enigmatic for decades, because fracture mechanics laws predict frictional resistance is too great for sliding to occur, except under rather unusual circumstances. The Miocene Mormon Peak detachment in Nevada and the Eocene Heart Mountain detachment in Wyoming are two well‐studied examples of upper crustal, carbonate‐hosted low‐angle detachments, with highly debated slip processes. Both low‐angle faults were active during regional magmatism, and a number of proposed slip mechanisms involve magmatic fluids, frictional heating, or both. To address the role that magmatic fluids and frictional heating may have played in reducing friction, we measured clumped‐isotope ratios on 137 carbonate samples from these faults. The majority of fault breccias and gouges on the detachment slip surface record temperatures that are colder than the host rock. Surprisingly, samples from within 5 m of the Heart Mountain detachment average just 65 °C, and not a single sample (out of 37 measurements, excluding metamorphosed host rock at White Mountain) records a temperature greater than 90 °C. Along both faults, most samples are depleted in δ 18 O relative to the host rock, indicating that meteoric, not magmatic, fluids were present and interacting with the fault rock. However, a few samples preserve temperatures of over 160 °C, which, based on textural and geochemical criteria, are difficult to explain other than by frictional heating during slip. These temperatures are recorded in one sample directly on the Mormon Peak detachment slip surface and in two hanging wall localities above the Heart Mountain detachment. Plain Language Summary: Some faults are oriented such that friction should prevent them from sliding, but show evidence of slip. Some of the potential explanations involve weakening processes that occur from heating on the fault, either from friction or from magmatic fluids. Here we use carbonate clumped‐isotope thermometry to look for heating signals preserved in the rock and use the carbon and oxygen isotopes to determine the source of the heat. We find that most of the rocks preserve a surprisingly cold temperature, while a small number do preserve a heating event that we interpret to be from friction. Key Points: Meteoric, not magmatic, fluids interacted with the low‐angle Mormon Peak and Heart Mountain detachments Clumped‐isotope thermometry can record a frictional heating signal, but it is rare on the Mormon Peak detachment and absent on the main Heart Mountain detachment Most fault breccias, gouges, and clastic dikes preserve temperatures that are colder than the host rock